2014
DOI: 10.1111/cpf.12145
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of moderate intensity aquatic exercise on coagulation factors in haemophiliacs

Abstract: The objective of this cross-sectional study was to analyse the acute effect of aquatic exercise on haemostasis in persons with haemophilia. Ten adult haemophiliacs (8 type A, 2 type B) familiarized with aquatic training performed a 20-min exercise session in a swimming pool at an intensity of ~70% maximum heart rate (HR). Blood samples were collected immediately after the training session. The haemostatic parameters selected for analyses were factor VIII (FVIII), prothrombin time (PT), activated partial thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In this study, we detected a pro-haemostatic response 5 min after moderate intensity exercise, and a reversal of these changes at 60 min in men with HA with baseline factor deficiencies of ≤10%. These findings are in keeping with other published studies [2,[4][5][6][7][8][9][10]. However, for the first time, we describe a sustainable increase in VWF:Ag and FVIII in men with HB, in contrast to men with HA.…”
supporting
confidence: 93%
“…In this study, we detected a pro-haemostatic response 5 min after moderate intensity exercise, and a reversal of these changes at 60 min in men with HA with baseline factor deficiencies of ≤10%. These findings are in keeping with other published studies [2,[4][5][6][7][8][9][10]. However, for the first time, we describe a sustainable increase in VWF:Ag and FVIII in men with HB, in contrast to men with HA.…”
supporting
confidence: 93%
“…Dynamic, isokinetic and isometric exercises are associated with improved muscle strength, proprioception and joint health, in addition to increasing social inclusion and adaptation (8)(9)(10). Additionally, studies in PWH have suggested a possible improvement in coagulation parameters including FVIII:C and von Willebrand factor (VWF) with exercise, suggesting that appropriate exercise, to a certain extent, might diminish the risk of bleeding (11)(12)(13). These studies, however, typically investigated small cohorts of subjects performing sub-maximal exercise; additionally, they did not use global haemostatic assays to assess coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…FVIII levels , or aggressive behavior of some animals. Evidence suggests that coagulation factors, including FVIII and VWF, significantly change after exercise . To demonstrate potential clinical usefulness, analyzes of blood from a healthy human control showed that, with the exception of the inter‐assay variation of the TGR, both intra‐assay and inter‐assay coefficients of variation of all TG parameters were < 15% (data not shown).…”
Section: Discussionmentioning
confidence: 99%